Faces of Holistic Mission : Stories of the OCMS Family (Book collections on Project MUSE., 2013)
There is a popular worship song that begins with the refrain "Look what the Lord has done, look what the Lord has done." This book does exactly that; it seeks to show what the Lord has done. Fifteen authors from five different continents identify what the Lord has indeed been doing, and continues to do, in their lives. They speak with passion, as each one seeks to bring glory to the Lord for his hand in their lives. Other than God's grace, the one constant that flows throughout these narratives is that at one point in their journey each author pursued a research degree via Oxford Centre for Mission Studies (OCMS) in order to further their very individual calling. These are their stories.